Seroepidemiology of trachoma in a low prevalence region receiving annual mass azithromycin distribution in Maradi, Niger. - Abdou Amza; Boubacar Kadri; Beido Nassirou; Ahmed Arzika; Elisabeth Gebreegziabher; Huiyu Hu; Lina Zhong; Cindi Chen; Danny Yu; Thomas Abraham; YuHeng Liu; Karana Wickens; et al. (PLoS Neglected Tropical Diseases)
Background Trachoma programs use the indicator trachomatous inflammation--follicular (TF) to monitor indication for and response to treatment for trachoma at the district level. Alternative indicators, including serologic markers, are increasingly being evaluated for trachoma surveillance. We evaluated seroprevalence of IgG antibodies to the Pgp3 antigen in two districts in Maradi, Niger thought to have low TF prevalence. Methods Data were collected as part of the baseline assessment of the Azithromycin Reduction to Reach Elimination of Trachoma (ARRET) trial in September 2021. A random sample of 80 communities was selected from Mayahi and Guidan Roumdji districts, both of which had TF prevalence <20% at their most recent trachoma impact survey in 2018. A random sample of 50 children per community was sampled. We collected field grades, conjunctival swabs for processing PCR for ocular Chlamydia trachomatis, and dried blood spots for serologic assessment. Results Of 3,994 children sampled in 80 communities, 49% were female and median age was 4 years. Overall TF prevalence was 4.6% (95% CI 3.5 to 5.8%) and trachomatous inflammation-intense (TI) prevalence was 0.6% (95% 0.3 to 0.9%). The prevalence of ocular chlamydia was 0.03% (95% CI 0.08%). Seroprevalence for Pgp3 antibodies was 6.3% (95% CI 5.5 to 7.1%) in 1-9-year-olds and 3.7% (95% CI 2.9 to 4.4%) in 1-5-year-olds. TF and Pgp3 seroprevalence were better correlated in 1-5-year-olds (correlation coefficient 0.29) compared to 1-9-year-olds (correlation coefficient 0.09). Conclusions In this low trachoma prevalence setting in Niger, seroprevalence of antibodies to Pgp3 were consistent with little ongoing transmission of C. trachomatis.